2017
DOI: 10.1177/0308022617733256
|View full text |Cite
|
Sign up to set email alerts
|

The state of play in children's occupational therapy: A comparison between Ireland, Sweden and Switzerland

Abstract: Introduction: Play is viewed as an important occupation in childhood and consequently in children's occupational therapy. However, few studies have explored the place of play in therapy practice. This study aimed to contribute to this knowledge gap by exploring play in occupational therapy in three European countries. Method: A cross-sectional survey of occupational therapists in Ireland, Sweden and Switzerland was conducted to examine the use of play with children under 12 years old. A web-based survey was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
4
25
0
5
Order By: Relevance
“…Several reasons were mentioned such as lack of knowledge on available play instruments and lack of continuing education on the existing play instruments. Lynch et al [18] in their survey found a similar finding where occupational therapists considered play important but indicated lack of education either from research, theory, evaluation, or intervention that contributed to challenges in applying play-centered practice. Meanwhile, Wadley and Stagnitti [19] found that occupational therapists and teachers do appreciate the importance of play for children; however, parents' and family members' understanding on the therapeutic value of play is limited and does not consider play the main goal for the children's functional outcome.…”
Section: Introductionmentioning
confidence: 80%
“…Several reasons were mentioned such as lack of knowledge on available play instruments and lack of continuing education on the existing play instruments. Lynch et al [18] in their survey found a similar finding where occupational therapists considered play important but indicated lack of education either from research, theory, evaluation, or intervention that contributed to challenges in applying play-centered practice. Meanwhile, Wadley and Stagnitti [19] found that occupational therapists and teachers do appreciate the importance of play for children; however, parents' and family members' understanding on the therapeutic value of play is limited and does not consider play the main goal for the children's functional outcome.…”
Section: Introductionmentioning
confidence: 80%
“…When practioners use instruments, they are most likely based on the ICF-CY body function and structure domain, especially with children with cerebral palsy (Saleh et al, 2008;Miller Kuhaneck et al, 2013). In studies of occupational therapy practice in three European countries (Ireland, Sweden and Switzerland), therapists all prioritised using assessments that examine functional skills over play (Lynch, Prellwitz, Schulze & Moore, 2018). This trend was evident despite a strong shared valuing of play as an essential occupation in childhood.…”
Section: Occupational Therapy Perspective On the Evaluation Of Playmentioning
confidence: 99%
“…O brincar é uma necessidade humana, sendo fundamental no desenvolvimento infantil 5 podendo ser usado para qualquer criança, hospitalizada ou não, desde que apropriado para as condições de saúde e adequado ao ambiente ao qual a criança está inserida no momento 6 . Na Terapia Ocupacional a brincadeira é vista como valiosa em si mesma e a habilidade de brincar da criança deve ser o foco da terapia, sendo reconhecido como evidência de realização intelectual e bem estar emocional [7][8] .…”
Section: Estudo De Caso Introduçãounclassified